Pengaruh Profitabilitas, Kebijakan Deviden, Dan Total Asset Turnover Terhadap Keputusan Investasi Pada Perusahaan Sub Sektor Otomotif dan Komponen Yang Terdaftar dI BEI - Abdul Jailani Manurung; Dian Ayu Andriani (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to determine the partial and simultaneous effects of Return on Assets (ROA), Dividend Payout Ratio (DPR), and Total Asset Turnover (TATO) on the Price Earnings Ratio (PER) in Automotive and Component Manufacturing Companies Listed on the Indonesia Stock Exchange. The population is 45 companies, and a sample of 8 companies, multiplied by 4 years of observation (2021-2024), yields 32 samples. Data analysis uses multiple linear regression. The results of the test (t), partially the Return On Asset Variable (X1) has a t-value of 2.191 with a significance level of 0.037 because the t-value> t-table is 2.191> 1.69913 and the significance value is 0.037 <0.05, meaning that H0 is rejected and H1 is accepted. Thus, it can be concluded that the ROA variable has an effect and is significant on the Price Earning Ratio. The Dividend Payout Ratio variable (X2) has a t-value of -2.100 with a significance level of 0.045 because the -t-value <-t-table is -2.100 <-1.69913 and the significance value is 0.05, so H0 is rejected and H1 is accepted..